PENGEMBANGAN PETUNJUK PEMBUATAN TEMPE DENGAN BAHAN BAKU KACANG HIJAU (Vigna radiate L.) DAN KACANG MERAH (Phaseolus vulgaris L.) - Faizah, Siti Rauhun; Gazali, Zulkarnain (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this research is to produce instructions for making tempeh with green beans and red beans that are suitable for use. Instructions for making tempeh were developed using the Thiagarajan 4D model reference. This research only uses 3 stages of development, namely define, design, and develop. The results of the validation and the results of field trials indicate that the instructions for making tempeh with raw materials of green beans and red beans are very feasible to use. Based on the results of the research, it can be said that product development in the form of instructions for making tempeh with raw materials of green beans and red beans is feasible.